Verbal Groups of Telic Action in Albanian Language - Prendushi, Gjilda Alimhilli (European Journal of Multidisciplinary Studies, 2017)
In this article I introduce and analyze the syntactic behaviour (compatibility and restrictions) of achievement and accomplishment verbs in standard Albanian, according to Aktionsart. The Aktionsart is a system of classification of verbs into verbal classes morphologically distinct from each other, in which at the basic meaning of the verb are added different values of space, quality, etc. The accomplishments and achievements in Albanian have comparable action meaning and syntactic behavior, such as to justify their inclusion in the class of telic verbs. A telic verb is that one which presents an action or event as being completed in some manner. On the other hand, these two subclasses of telics are also characterized on the basis of a series of distinctive elements that lead us to lay a certain distinction between them. An accomplishment verb is a form that expresses that something or someone has undergone a change in state as the result of the completion of an event. On the other side an achievement verbs express an instant action that changes the state of the subject. By using the categories and procedures of textual linguistics I focus on the semantic and syntactic features of some groups of verbs.